'This magical Tudor house': Cotehele and the Concept of Authenticity: A Chronological Review. (1st May 2009) - Busby, Graham; Hunt, Rachel; Small, Helen
Cotehele is a National Trust (NT) estate of some 1, 289 acres, in Cornwall, bounded by the river Tamar, which is the border with Devon. The official guide book begins the description of the house with the following: 'This magical Tudor house, hidden away in the valley of the Tamar and even today accessible only by a network of narrow lanes, is a rare survival.' But a survival of what? Much of the building occurred between 1485 (the year of Bosworth Field, beneficial to the family fortunes) and 1539; furthermore, the property is said to be 'unique in showing few obvious signs of rebuilding since the mid-seventeenth century'. While Cotehele is a substantial estate, visitor numbers are not high, fluctuating between 77, 000 and 85, 000 most years; perhaps, its location explains why it does not receive the numbers achieved by other Cornish NT properties. On the other hand, a greater volume of visitors would undoubtedly affect the fabric of this property. Following an examination of the concept of authenticity, this paper reviews how Cotehele has been presented over the centuries by identifying a specific activity, in each of three centuries, and reflecting on how this has a bearing on what the visiting public experience. Finally, data from a substantial on-site survey is incorporated in order to examine the contemporary visitors' perception of authenticity of the site/sight.